Portraits of the missive writer as a young man: Figurations of the modern artist in james joyce's love correspondence - De Andrade, Rangel Gomes [UNESP]; Vicente, Adalberto Luis [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2021)
In this paper, we approach Irish writer James Joyce's love epistolography addressed to his wife Nora Barnacle departing from the personas the writer develops in his letters. These epistolary personas, themselves representations of the modern artist as produced by Romantic-Symbolist aesthetics, manifest themselves as masks adopted by Joyce in the letter's scenographic stage. We first prioritize a theoretical perspective of the let ter as a performatic process marked by the staging and masquerading of the self. Hereinafter, we present the Joycean love correspondence and its context of production, aiming to analyze the personas that are expressed in these letters, in particular the social and literary figures of the outsider and the dandy, and with which Joyce covers his epistolary enunciation.
Retratos do missivista quando jovem: Figurações do artista moderno na correspondência amorosa de james joyce
Keywords: Dandy; Epistolary genre; James joyce; Outsider; Persona